Brain mechanisms for processing affective touch - Gordon, Ilanit (Hum Brain Mapp, 2011)
Despite the crucial role of touch in social development, there is very little functional magnetic resonance imaging (fMRI) research on brain mechanisms underlying social touch processing. The “skin as a social organ” hypothesis is supported by the discovery of C‐tactile (CT) nerves that are present in hairy skin and project to the insular cortex. CT‐fibers respond specifically well to slow, gentle touch such as that which occurs during close social interactions. Given the social significance of such touch researchers have proposed that the CT‐system represents an evolutionarily conserved mechanism important for normative social development. However, it is currently unknown whether brain regions other than the insula are involved in processing CT‐targeted touch. In the current fMRI study, we sought to characterize the brain regions involved in the perception of CT‐supported affective touch. Twenty‐two healthy adults received manual brush strokes to either the arm or palm. A direct contrast of the blood‐oxygenation‐level‐dependent (BOLD) response to gentle brushing of the arm and palm revealed the involvement of a network of brain regions, in addition to the posterior insula, during CT‐targeted affective touch to the arm. This network included areas known to be involved in social perception and social cognition, including the right posterior superior temporal sulcus and the medial prefrontal cortex (mPFC)/dorso anterior cingulate cortex (dACC). Connectivity analyses with an mPFC/dACC seed revealed coactivation with the left insula and amygdala during arm touch. These findings characterize a network of brain regions beyond the insula involved in coding CT‐targeted affective touch. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.